The Effect Of Personal Selling And Advertising On Increasing The Sales Volume Of Honda CBR 250r Motorcycles At Bintang Mulia Jaya Lahat Dealers - M Rafli Askola; Heri Fitriadi; Delvina Yulanda (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine how personal selling and advertising partially and simultaneously influence the increase in sales volume of the Honda CBR 250R motorcycle at the Bintang Mulia Jaya Lahat dealership. The sample size for this study was 33 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis , processed using SPSS software, resulting in a regression equation. The results showed a significant effect of personal selling on the increase in sales volume of the Honda CBR 250R motorcycle at the Bintang Mulia Jaya Lahat dealership. The F-test showed that personal selling and advertising simultaneously influenced the increase in sales volume of the Honda CBR 250R motorcycle at the Bintang Mulia Jaya Lahat dealership.